2022
DOI: 10.1186/s13613-022-01017-5
|View full text |Cite
|
Sign up to set email alerts
|

Does the cytokine adsorber CytoSorb® reduce vancomycin exposure in critically ill patients with sepsis or septic shock? a prospective observational study

Abstract: Background Hemadsorption of cytokines is used in critically ill patients with sepsis or septic shock. Concerns have been raised that the cytokine adsorber CytoSorb® unintentionally adsorbs vancomycin. This study aimed to quantify vancomycin elimination by CytoSorb®. Methods Critically ill patients with sepsis or septic shock receiving continuous renal replacement therapy and CytoSorb® treatment during a prospective observational study were included… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A prospective observational study in seven patients with septic shock demonstrated significant adsorption of vancomycin by a resin adsorber cartridge, with a linear decrease during HA with the CytoSorb ® cartridge [6]. The authors proposed an additional 500 mg dose of vancomycin over 2 h at the initiation of HA to compensate for removal by the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational study in seven patients with septic shock demonstrated significant adsorption of vancomycin by a resin adsorber cartridge, with a linear decrease during HA with the CytoSorb ® cartridge [6]. The authors proposed an additional 500 mg dose of vancomycin over 2 h at the initiation of HA to compensate for removal by the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, albumin or coagulation factors are not removed, however, certain drugs, e.g. vancomycin are removed [ 8 ]. A detailed list of adsorbed substances is given in Scheier et al and for specific drugs, therapeutic drug monitoring is recommended [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence assessing the pharmacokinetic behavior of antibiotics typically used in patients undergoing hemoperfusion is limited, and only a few data exist coming from small and heterogeneous studies [67][68][69][70][71][72]. Due to the critical importance of optimal antimicrobial treatment in sepsis, it seems crucial to understand and compensate for such extracorporeal loss during Fig.…”
Section: Open Questions: Research Methodology Unwanted Drug Clearance...mentioning
confidence: 99%
“…Consequently, additional extra doses of antimicrobials must be administered within the first few hours of initiation of hemoperfusion to maintain a clinically adequate steady-state serum concentration. A recent prospective observational study, designed to quantify the adsorption of vancomycin (as a continuous infusion with a preceding loading dose over 2 h) by CytoSorb ® , demonstrated significant adsorption of vancomycin with a linear decrease during CytoSorb ® treatment [69]. A total of 160 vancomycin serum samples from 7 patients with septic shock were included in the analysis and 15% of the samples were collected during CytoSorb ® treatment.…”
Section: Open Questions: Research Methodology Unwanted Drug Clearance...mentioning
confidence: 99%